Word processing for business publications : how to produce proposals, manuals, catalogs, newsletters, and more - Holtz, Herman (New York : McGraw-Hill, 1985)
The book provides a guide for making the best use of the word processing system. The focus is on word processing applications and use in writing and editorial process
Includes index.
II 15/01/2019
Loans
Keywords: Word processing; Business literature; Newsletters; Catalogs